Methotrexate in the treatment of peripheral arthritis in ulcerative colitis - R. Scarpa; F. Manguso; M. Lofrano; M. Raimodo; L. Costa; F. Caso; V. Bruner; S. Iervolino; M. Atteno; R. Peluso (PAGEPress Publications, 2011)
Objective: To evaluate efficacy of methotrexate treatment in peripheral arthritis of ulcerative colitis. Methods: We studied 18 patients (10/8 M/F; mean age: 38.90 yrs; range: 21-65 yrs), with peripheral arthritis (14 with polyarticular, 4 with oligoarticular subset) associate ulcerative colitis. Methotrexate 20 mg/week was administered in our patients, who were already receiving mesalazina for inflammatory bowel disease. At baseline, after 3 (T1), 6 (T2) and 12 months (T3) serological parameters (ESR and CRP), functional status (HAQ) and disease activity (VAS, GH, Ritchie articular index) were evaluated. Results: During the therapy a significant improvement was observed in disease activity, functional status and serological parameters since T1. ESR and CRP did not change at T2 and T3. Instead VAS, GH, Ritchie articular index and HAQ had a significant and gradual improvement from T1 to T3. Conclusion: Methotrexate treatment was efficacious in the treatment of peripheral arthritis associate ulcerative colitis. This drug induced improvement in disease activity, functional status and serological parameters after 3 months of therapy.